Analisis Perbandingan Rasio Profitabilitas Bank Muamalat Sebelum dan Sesudah Penerapan Muamalat Mobile dan Muamalat Digital Islamic Network (DIN) - Wibowo , Dedi; Wanakusuma, Ilham Wanakusuma; Simamora, Saur C. (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
The purpose of this study is to determine the difference in profitability of Bank Muamalat before and after the implementation of mobile banking. The observation period for this study is seven years before (2009-2015) and after (2016-2022) the implementation of mobile banking. The methods used are quantitative to measure ROA, ROE, NOM, and BOPO ratios. Hypothesis testing was performed using the paired-samples t-test and the Wilcoxon signed-rank test, depending on the results of the normality test of the data. The study shows that the implementation of mobile banking has led to significance difference in overall ratios, with ROA, ROE, and NOM ratios decreasing, and BOPO ratios increasing.